Stabilization and control of autonomous hexacopter via visual-servoing and cascaded-proportional and derivative (PD) controllers - Ahmed, O. A.; Latief, Marsad; Ali, M. A.; Akmeliawati, Rini (2015)
In this paper, a new integrated control system via visual-servoing and cascaded proportional derivative (PD) controllers for an autonomous hexacopter is proposed. The spherical image based visual servoing is designed to control the hexacopter to the desired pose with respect to an arbitrary target in three-dimensional (3D) workspace based on images captured. Meanwhile, the cascade-PD controller is designed to stabilize and to control the altitude and heading of the hexacopter. The proposed control strategy is compared with the nested saturation control laws which are adapted to control the horizontal trajectory of the vehicle along X and Y-axes. Simulation results show the ability of the proposed controller in driving the unmanned aerial vehicle (UAV) to the desired pose successfully. The performance of the proposed controllers outperforms the nested saturation controller in tracking a fixed target.